2021
DOI: 10.1016/j.jcmg.2020.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Diagnostic Reference Levels for Single-Photon Emission Computed Tomography Myocardial Perfusion Imaging

Abstract: Objectives: To establish worldwide and regional diagnostic reference levels (DRLs) and achievable administered activities (AAAs) for SPECT MPI.Background: Reference levels serve as radiation dose benchmarks to compare individual laboratories against aggregated data, helping to identify sites in greatest need of dose reduction interventions. DRLs for SPECT myocardial perfusion imaging (MPI) have previously been derived from national or regional registries. To date there have been no multi-regional reports of DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…7,13,[24][25][26] Given the frequent and widespread use of SPECT imaging to risk-stratify patients for coronary artery disease, the use of SPECT imaging findings in this fashion could potentially result in earlier diagnosis of pulmonary vascular disease and improved clinical outcomes in a significant number of patients. 27,28 In our study we also observed a significant association with Black race and risk of echocardiographic PH among patients with low-risk SPECT studies. However, after evaluating our model for the interaction between race and incidental RV abnormalities on SPECT imaging, no significant relationship was observed (Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…7,13,[24][25][26] Given the frequent and widespread use of SPECT imaging to risk-stratify patients for coronary artery disease, the use of SPECT imaging findings in this fashion could potentially result in earlier diagnosis of pulmonary vascular disease and improved clinical outcomes in a significant number of patients. 27,28 In our study we also observed a significant association with Black race and risk of echocardiographic PH among patients with low-risk SPECT studies. However, after evaluating our model for the interaction between race and incidental RV abnormalities on SPECT imaging, no significant relationship was observed (Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…analyzed variations in regional doses, diagnostic reference levels, and adherence to best practices (17,(19)(20)(21)(22)(23)(24)(25), but have not evaluated specific technologies. In this study, we compare regional utilization of camera technologies, advanced post-processing software, and imaging protocols and their impact on patient radiation dose.…”
Section: Nuclear Cardiology Protocols Study (Incaps) Previous Incaps ...mentioning
confidence: 99%
“…Indeed, the primary challenge for MPI procedures is designing an MPI protocol that delivers the lowest radiation burden necessary to acquire adequate diagnostic image quality via NM administered activity during SPECT or PET and the CT component of SPECT/CT and PET/CT scans [ 7 , 8 ]. To facilitate the dose reduction process, the concept of diagnostic reference levels (DRLs) has emerged as a gauge for monitoring the radiation doses of diagnostic medical imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the majority of NDRL reports focus on reporting administered activity from only MPI SPECT or MPI PET scans, with only a few identified studies reporting NDRLs for the CT component of these examinations [ 9 ]. Furthermore, the literature review highlighted that variation in NDRL value for the administered activities related to the stress and rest one-day protocol range from 407 MBq and 740 MBq to 555 MBq and 1184 MBq for 99m Tc-Tetrofosmin /Sestamibi, respectively [ 8 , 11 , 12 ]. Regarding CT components, a few articles reflect the change of variation in NDRL related to the CT dose, for instance, the CTDI vol value ranges from 2.2 mGy to 36 mGy and the DLP value ranges from 36 mGy.cm to 380 mGy.cm [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%